Water-based drilling fluid friction reducing agent containing nanometer material and preparation method of water-based drilling fluid friction reducing agent

By combining modified rapeseed oil and nanomaterials, a high-temperature-resistant water-based drilling fluid friction reduction resistor was prepared, which solved the problems of insufficient stability, compatibility and environmental protection in the prior art, and achieved the effect of efficiently reducing friction resistance and improving drilling efficiency.

CN120248847APending Publication Date: 2025-07-04CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510150021.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

The existing water-based drilling fluid friction reducing agents are insufficient in high temperature and complex chemical environments, have poor compatibility, poor thermal stability, insufficient environmental protection, and cannot effectively solve the friction problem between the drill string and the drilling fluid.

Method used

Rapeseed oil is used as the base oil, and sulfur ions are introduced and esterified with aluminum oxide, iron oxide, magnesium oxide, etc. at high temperature. Nano-tungsten disulfide modified by N-hydroxysuccinimide is added to form a lubricating film that resists high temperatures, improves lubricating performance and stability, and uses NHS activation technology to improve the dispersion and adhesion of nanomaterials.

Benefits of technology

It improves the strength and toughness of the lubricating film, reduces friction resistance, enhances the temperature resistance and environmental protection of the drilling fluid, improves the drilling efficiency and environmental friendliness, and solves the stability and compatibility of the drilling fluid in high temperature and complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120248847A_ABST
    Figure CN120248847A_ABST
Patent Text Reader

Abstract

The invention provides a nano-material-containing water-based drilling fluid friction reducing agent and a preparation method thereof, rapeseed oil is selected as a raw material of base oil, sulfur ions are grafted into a structure in a modification mode, and vulcanized rapeseed oil base oil is prepared; selecting aluminum oxide, iron oxide and magnesium oxide to generate esterification reaction under high-temperature catalysis, putting a friction reducing agent sample into a water bath kettle which is preheated in advance, and adding glyceryl stearate to prepare an additive; the preparation method comprises the following steps: under a water bath heating condition, adding NHS into DCC, reacting the NHS with the DCC to generate active ester, and under an oil bath heating condition, adding the activated NHS into rapeseed oil containing nano tungsten disulfide, stirring and reacting to prepare NHS modified nano tungsten disulfide; the additive and NHS-modified nano tungsten disulfide are slowly added into preheated sulfurized rapeseed oil base oil in an oil bath pan in proportion, stirring reaction is performed, and the water-based drilling fluid friction reducing agent is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water-based drilling fluid friction reducers, and specifically to a water-based drilling fluid friction reducer containing nanomaterials and a preparation method thereof. Background Art

[0002] Drilling fluid plays a crucial role in drilling operations. It can not only carry cuttings and cool the drill bit, but also stabilize the wellbore and prevent drilling accidents.

[0003] However, with the increase in drilling depth, the bottom-hole geological conditions become complex, and conditions such as temperature and pressure become more and more harsh. The problem of frictional resistance of drilling fluid becomes increasingly prominent, seriously affecting the drilling speed and drilling efficiency.

[0004] In order to solve the problem of excessive frictional resistance of drilling fluid, the research and application of friction reducers have become an urgent need. As a chemical substance that can reduce the viscosity and frictional resistance of drilling fluid, water-based drilling fluid friction reducers have gradually attracted extensive attention in the industry. It effectively reduces the wear of the drill bit and drill pipe by changing the physical and chemical properties of the drilling fluid, improves the drilling speed, thereby shortening the drilling time and reducing the drilling cost.

[0005] In recent years, with the development of unconventional oil and gas resources such as shale gas, the requirements for drilling fluid technology have become higher and higher. Significant progress has been made in high-performance water-based drilling fluid technology. As a key component, the performance of friction reducers is also constantly improving. At the same time, with the increasingly strict environmental protection regulations, the environmental friendliness of friction reducers has also become the focus of research and development. Modern friction reducers gradually use degradable or low-toxic raw materials to reduce environmental pollution.

[0006] Water-based drilling fluid friction reducers have been widely used in drilling fluids in fields such as oil, natural gas, geothermal energy, and water wells. It can not only effectively improve the drilling speed, but also reduce the wear of the drill bit, lower the drilling cost, and at the same time play a positive role in reducing the bottom-hole temperature, stabilizing the wellbore, and preventing drilling accidents.

[0007] The working principle of nano friction reducers includes the following aspects: First, through their unique size effect and surface effect, nano particles can form a stable dispersion system in the drilling fluid, improving the lubrication performance of the drilling fluid; Second, nano particles can penetrate into the formation pores, interact with the pore wall surface, and form a lubricating film to reduce the friction coefficient between the drill string and the formation; Finally, nano particles can also form a plugging layer in the formation pores to prevent further loss of drilling fluid and protect the formation environment.

[0008] Defects and deficiencies of the prior art:

[0009] 1. Problem of performance stability

[0010] The friction reducer for water-based drilling fluid needs to maintain stable performance during the drilling process to ensure its continuous and effective reduction of frictional resistance. However, during the operation of the drilling fluid, the liquid temperature will continuously rise, and the salts and acidic substances that may exist in the drilling fluid may cause hydrothermal degradation of the friction reducer, resulting in a decline in its performance. Therefore, how to improve the stability of the friction reducer in high-temperature and complex chemical environments is an important technical issue.

[0011] 2. Compatibility issues

[0012] The friction reducer needs to have good compatibility with other components in the drilling fluid (such as base mud, inhibitors, etc.) to ensure that the overall performance of the drilling fluid is not affected. If the friction reducer is incompatible with other components, it may cause changes in the rheology and filtration properties of the drilling fluid, and even lead to drilling accidents. Therefore, studying the compatibility of the friction reducer with other components in the drilling fluid is the key to ensuring its effective application.

[0013] 3. Thermal stability issues

[0014] In a high-temperature drilling environment, the thermal stability of the friction reducer becomes a key factor affecting its performance. If the friction reducer decomposes or deteriorates at high temperatures, it will not only lose its friction-reducing effect, but may also have a negative impact on other properties of the drilling fluid. Therefore, how to improve the thermal stability of the friction reducer so that it can still maintain stable performance in a high-temperature environment is another technical issue that needs to be solved.

[0015] 4. Environmental protection issues

[0016] With the increasingly strict environmental protection regulations, the environmental protection of drilling fluid has also become an increasingly important consideration. As an important component of drilling fluid, the environmental protection of the friction reducer for water-based drilling fluid also needs to be concerned. Traditional friction reducers may contain chemicals harmful to the environment. Therefore, developing environmentally friendly friction reducers to reduce their pollution and harm to the environment is the future development trend.

[0017] 5. Coping with the problem of friction generated between the drill string and the drilling fluid

[0018] Due to the friction between solids and liquids, a large amount of friction is easily generated between the drill string and the drilling fluid, which affects the normal drilling efficiency. At present, it is difficult to solve the friction existing between the drill string and the drilling fluid caused by rotation. Summary of the Invention

[0019] In view of the problems of poor environmental protection of the friction reducer for water-based drilling fluid, instability of the friction-reducing performance due to changes in the type of drilling fluid and drilling environment, and the inability to fundamentally solve the friction generated between the drill string and the drilling fluid, the present invention proposes a preparation method of a friction reducer for water-based drilling fluid containing nanomaterials, including the following steps:

[0020] S1. Select rapeseed oil as the raw material of the base oil, and introduce sulfur ions into the structure through a modification method to prepare a sulfurized rapeseed oil base oil;

[0021] S2. Select alumina, iron oxide and magnesium oxide to carry out an esterification reaction under high-temperature catalysis. Put the friction reducer sample into a preheated water bath, and add the pre-prepared glyceryl stearate to adjust the viscosity of the drilling fluid to prepare an additive;

[0022] S3. Under the condition of water bath heating, add N-hydroxysuccinimide to N,N'-dicyclohexylcarbodiimide. N-hydroxysuccinimide reacts with N,N'-dicyclohexylcarbodiimide to form an active ester. Then, under the condition of oil bath heating, add the activated N-hydroxysuccinimide to rapeseed oil containing nano tungsten disulfide and stir to react to obtain N-hydroxysuccinimide-modified nano tungsten disulfide;

[0023] S4. Slowly add the additive obtained in step S2 and the N-hydroxysuccinimide-modified nano tungsten disulfide obtained in step S3 into the sulfurized rapeseed oil base oil preheated in an oil bath, and stir to react to obtain a water-based drilling fluid friction reducer.

[0024] In a preferred embodiment, in step S2, the mass fraction of alumina is 0.1%, the mass fraction of iron oxide is 0.02%, and the mass fraction of magnesium oxide is 0.2%; the mass fraction of glyceryl stearate is 7%.

[0025] In a preferred embodiment, in step S3, under the condition of a water bath at 80 °C, add N-hydroxysuccinimide to N,N'-dicyclohexylcarbodiimide, stir and react at 500 r / min for 6 h. Under the condition of oil bath heating at 120 °C, add 10 ml of activated N-hydroxysuccinimide to rapeseed oil containing 20% nano tungsten disulfide by mass and stir and react at 500 r / min for 6 h to obtain N-hydroxysuccinimide-modified nano tungsten disulfide.

[0026] In a preferred embodiment, in step S4, the sulfurized rapeseed oil base oil is preheated to 120 °C and stirred and reacted at 500 r / min for 6 h.

[0027] In a preferred embodiment, in step S2, the esterification reaction equation is as follows:

[0028] XO + 2R-COOH → (catalyst, heating) X(R-COO)2 + H2O.

[0029] In a preferred embodiment, in step S1, the mass fraction addition ratios are 0.1% alumina powder, 0.02% iron oxide powder, 0.2% magnesium oxide powder, 5% NHS-modified nano tungsten disulfide, and 7% glyceryl stearate.

[0030] The present invention also provides a water-based drilling fluid friction reducer containing nanomaterials prepared by the preparation method of the water-based drilling fluid friction reducer containing nanomaterials described above, using rapeseed oil as the base oil raw material; the main chain of the molecular structure of the water-based drilling fluid friction reducer is a C-C single bond structure, and the average bond energy of the C-C single bond is 347.3 kJ / mol. Sulfur elements are incorporated into the structure through a sulfidation method to form S═C═S or S≡C≡S bonds. The bond energy of the carbon-sulfur double bond is 536 kJ / mol, and the bond energy of the carbon-sulfur triple bond is 577 kJ / mol to obtain high-temperature-resistant sulfurized rapeseed oil; at the same time, Fe, Al, and Mg elements are incorporated into the polymer to form metal bonds and covalent bonds between carbon and metals to form a lubricating film, and finally NHS-modified nano tungsten disulfide is added.

[0031] Compared with the prior art, the present invention has the following beneficial technical effects:

[0032] (1) By incorporating sulfur ions into the polymer structure, the present invention can greatly improve the strength of the lubricating film, and at the same time, sulfur elements can improve the high-temperature resistance of the friction reducer, thereby improving the performance of the drilling fluid.

[0033] (2) By incorporating metal ions into the polymer structure, the present invention improves the strength and toughness of the lubricating film, reduces the frictional resistance, improves the friction reduction performance of the drilling fluid, and improves the drilling efficiency.

[0034] (3) The selection of rapeseed oil, which belongs to vegetable oil, as the base oil raw material can greatly improve the environmental pollution problems caused by the use of mineral oil in common friction reducers.

[0035] (4) Innovatively using nanomaterials and using NHS activation technology to improve their dispersibility and adhesion on the surface of N80 steel greatly improves the frictional resistance between the drilling fluid and the drill string surface. Description of the Drawings

[0036] Figure 1 N80 steel sheet after adsorption in the drilling fluid without a friction reducer containing nano additives;

[0037] Figure 2 N80 steel sheet after adsorption in the drilling fluid with a friction reducer containing nano additives;

[0038] Figure 3 SEM result of adsorption in the drilling fluid without a friction reducer containing nano additives;

[0039] Figure 4 SEM results of adsorption in drilling fluid containing nano-additive friction reducer

[0040] Figure 5 Variation of lubrication coefficient of friction reducer samples with different proportions added Specific implementation mode

[0041] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0042] The molecular structure design of the water-based drilling fluid friction reducer LZA-818 is based on the following principles: (1) The main chain adopts a C-C single bond structure, and the average bond energy of the C-C single bond is 347.3 kJ / mol, which is not easily degraded at high temperatures; (2) Incorporate S element into the structure to form S=C=S or S≡C≡S bonds, which increases the bond energy, that is, improves the high-temperature resistance; (3) Incorporate Fe, Al, and Mg elements into the polymer, which can enhance its tensile strength and impact toughness, improve the lubricating film strength, and also improve the thermal stability of the polymer; (4) When NHS active ester is used to modify the nanomaterial, NHS active ester groups can be introduced on the surface of the nanomaterial, which can effectively improve its adsorption on the N80 steel surface. In addition, NHS modification can also improve the dispersion of the nanomaterial in aqueous solution.

[0043] 1. Selection and modification of base oil

[0044] Through orthogonal experiments, rapeseed oil was comprehensively selected as the raw material of the base oil from soybean oil, rapeseed oil, and white oil according to their physical and chemical properties and the indicators such as the lubrication coefficient and viscosity of the drilling fluid after adding to the drilling fluid. However, due to the need to improve its high-temperature resistance, S ions need to be incorporated into the structure through a modification method to prepare sulfurized rapeseed oil.

[0045] 2. Screening of conventional additives

[0046] Select alumina, iron oxide, and magnesium oxide, and use orthogonal experiments to measure the optimal proportions of adding them to the friction reducer as 0.1% alumina, 0.02% iron oxide, and 0.2% magnesium oxide. At the same time, the above materials undergo an esterification reaction under high-temperature catalysis, improving their stability in the friction reducer. The reaction equation is as follows:

[0047] XO + 2R-COOH → (catalyst, heating) X(R-COO)2 + H2O

[0048] Put the friction reducer sample into a water bath preheated to 80°C in advance, and add 7% glyceryl stearate to adjust the viscosity and shear force of the drilling fluid.

[0049] 3. Screening and modification of nano additives

[0050] 1) Material selection

[0051] Select nano molybdenum disulfide and nano tungsten disulfide as alternative nano materials, and through orthogonal experiments, it is found that the friction reduction performance of nano tungsten disulfide is relatively excellent, and the optimal addition amount is 3%. Then, from a microscopic perspective, explore the influence of the microscopic shape of nano tungsten disulfide particles on the performance of the friction reducer. Select spherical-like and flaky as alternative conditions. Finally, it is obtained that adding 3% spherical-like nano tungsten disulfide by mass fraction is most helpful for improving the performance of the friction reducer.

[0052] 2) Modification of nano tungsten disulfide

[0053] First, under the condition of 80°C water bath, add NHS to DCC and stir and react at 500 r / min for 6 h. NHS reacts with DCC to form an active ester, which can react with compounds containing amino groups to form stable amide bonds. The role of DCC is to promote the activation of NHS, making it easier to combine with amino compounds to form activated NHS. Then, under the condition of 120°C oil bath heating, add 10 ml of activated NHS to rapeseed oil containing 20% nano tungsten disulfide by mass fraction and stir and react at 500 r / min for 6 h to prepare NHS-modified nano tungsten disulfide, whose adsorption and dispersion are greatly improved compared with ordinary nano tungsten disulfide solid.

[0054] (3) Preparation of water-based drilling fluid nano friction reducer LZA-818

[0055] Slowly add the above conventional additives and nano additives according to the mass fraction addition amount of 0.1% aluminum oxide powder + 0.02% iron oxide powder + 0.2% magnesium oxide powder + 5% NHS-modified nano tungsten disulfide + 7% glyceryl stearate to the sulfurized rapeseed oil base oil preheated to 120°C in an oil bath pot and stir and react at 500 r / min for 6 h. The dark brown oily liquid obtained is the LZA-818 friction reducer.

[0056] 4. Performance test of LZA-818 friction reducer

[0057] (1) Test on the relationship between the performance of LZA-818 and its addition amount

[0058] Add LZA-818 with mass fractions of 0.2%, 0.3%, 0.4%, 0.5%, and 0.6% respectively to 5.0% fresh water base slurry, and use a high-speed stirrer to stir at 10,000 r / min for 20 min, and test its performance before and after aging at 120 °C for 16 h in the base slurry.

[0059] Table 2-1 Performance testing of LZA-818 with different dosages in freshwater slurry

[0060]

[0061] As can be seen from the results shown in Table 2-1: The LZA-818 friction reducer improves the lubricity of the experimental slurry and has moderate thermal stability. As the temperature rises, its ability to improve lubricity decreases slightly; the shear force data increases with the increase in the dosage of LZA-818, and the viscosity data also increases slightly, indicating that the strength of the network structure inside the experimental slurry fluid and the strength of the lubricating film increase.

[0062] In summary, the LZA-818 friction reducer can play an obvious anti-friction and lubricating role, achieving the purpose of reducing friction, and the anti-friction and lubricating effect is proportional to the dosage.

[0063] 5. Anti-temperature, anti-salt and anti-calcium tests of LZA-818

[0064] (1) Anti-temperature of LZA-818

[0065] Test the performance of the LZA-818 friction reducer added to 5.0% fresh water base slurry before and after aging at different temperatures.

[0066] Table 2-2 Performance testing of LZA-818 friction reducer in freshwater slurry before and after aging at different temperatures

[0067]

[0068]

[0069] The test results are shown in Table 2-2. After adding the LZA-818 friction reducer, the lubrication coefficient of the experimental slurry decreased significantly before aging, and the decrease rate reached 42.18%. When the aging temperature was between 120°C and 150°C, the lubrication coefficient decreased relatively fast. Compared with the fresh water base slurry, the decrease rate of the lubrication coefficient reached 74.83%. In summary, LZA-818 has good temperature resistance and can maintain relatively stable properties in the high-temperature downhole environment.

[0070] (2) Salt and calcium resistance performance test of nano friction reducer

[0071] Take a certain amount of fresh water base slurry and add 3% LZA-818 friction reducer. After high-speed stirring for 20 min, it is the experimental slurry. Add gradient concentrations of NaCl and CaCl2 to the experimental slurry, continue high-speed stirring for 20 min, measure the lubrication coefficient of the base slurry, and measure and evaluate the salt and calcium resistance of the experimental slurry again after aging at 150°C for 16 h.

[0072] Table 2-3 Performance testing of LZA-818 friction reducer in freshwater slurry containing different concentrations and types of salts

[0073] containing different concentrations and types of salts

[0074]

[0075]

[0076] The experimental results are shown in Table 2-3. The lubrication coefficient of the experimental slurry before and after aging increased with the increase of the NaCl content, and both the static shear force and the dynamic shear force of the experimental slurry increased. The reason is that after the drilling fluid is invaded by salt, the diffusion double layer of the compressed clay is compressed, its potential decreases, the hydration film becomes thinner, and a network structure is formed between the clay particles, resulting in an increase in the shear force; the apparent viscosity and plastic viscosity of the experimental slurry remained stable with only a small increase. Therefore, the NaCl environment will affect the performance of LZA-818, and the influence is positively correlated with the concentration. Similar to the above NaCl influence test results, the CaCl2 environment will affect the performance of LZA-818, and the influence is positively correlated with the concentration. However, the influence on the friction reduction ability of LZA-818 is less than that of the NaCl environment.

[0077] In summary, the LZA-818 friction reducer has good salt and calcium resistance performance.

[0078] 6. Adsorption Test of LZA-818 Friction Reducing Agent Nanoparticles

[0079] Take two identical N80 steel sheets and place them in drilling fluids without and with nano-additive friction reducing agent respectively for adsorption for 4 hours. After the adsorption is completed, wash the visible drilling fluid components on the surface with deionized water and dry them to obtain the following results.

[0080] As Figure 1 、 2 shown are the N80 steel sheets after adsorption in the drilling fluid without nano-additive friction reducing agent and the N80 steel sheets after adsorption in the drilling fluid with nano-additive friction reducing agent

[0081] The working principle of a Scanning Electron Microscope (SEM) is as follows: A focused high-energy electron beam scans the surface of the sample to generate various information (secondary electrons, backscattered electrons, transmitted electrons, absorbed electrons, etc.). This information is amplified by the detector receiving and amplifying unit and then fed back to the display. The electron beam and the display are scanned synchronously to achieve the imaging purpose. Because the SEM can directly observe the original surface of rock samples, it has the characteristics of large depth of field, strong three-dimensional sense of the image, relatively high resolution, and large magnification, and is a commonly used means for qualitative analysis of clay minerals. Therefore, observing the type, crystal morphology, and occurrence of clay minerals through SEM is one of the important means for reservoir evaluation and determining reservoir protection measures.

[0082] Using SEM, the morphology, distribution, properties, and symbiotic combination of the solid surface can be observed, so as to analyze the adsorption situation and adsorption morphology of substances on the solid surface, which is conducive to making a more comprehensive evaluation of the adsorption property later.

[0083] The microscopic structure of the surface of the N80 steel sheet was tested using a Hitachi S4800 cold field emission scanning electron microscope. The test results are shown in Figure 3 、 Figure 4 。

[0084] From Figure 3 it can be clearly seen that at a magnification of 1000 times, there are only bright rust marks on the surface of the N80 steel sheet after adsorption in the drilling fluid without nano-additive friction reducing agent, and there are no obvious modified nano tungsten disulfide particles. At the same time, at a magnification of 10000 times, there are also no obvious particle adsorptions.

[0085] Compared with Figure 3 in Figure 4It can be clearly seen that at a magnification of 1000 times, on the surface of the N80 steel sheet adsorbed in the drilling fluid containing the nano-additive friction reducer, there are obvious high-brightness rust marks, and at the same time, there are a large number of modified nano tungsten disulfide particles, which are densely distributed, with a distribution rate exceeding 90% and a net adsorption area exceeding 25%. At the same time, at a magnification of 10000 times, more modified nano tungsten disulfide particles can also be seen.

[0086] It can be seen from this that the modified nano tungsten disulfide is more likely to be adsorbed on the surface of the N80 steel sheet.

[0087] 7. Performance comparison between LZA-818 and common friction reducers

[0088] LZA-818 was horizontally compared with the domestic and foreign high-temperature and high-salt-resistant friction reducers with good performance, and the performance of each friction reducer in the corresponding base slurry was tested at different aging temperatures. Four friction reducers with better performance were respectively added to experimental slurries 1-1 to 1-4 and 2-1 to 2-4, and the LZA-818 friction reducer was added to experimental slurries 1-5 and 2-5 to compare their performance differences.

[0089] Table 2-4 Comparison of the performance of different types of traditional friction-reducing agents and LZA-818 friction reducing agent before and after aging

[0090]

[0091]

[0092] According to Table 2-4, the LZA-818 friction reducer has an obvious effect on reducing the lubrication coefficient of the drilling fluid in a fresh water environment. At the same time, when the LZA-818 friction reducer is added to the drilling fluid in a fresh water environment, the values of the static shear force and dynamic shear force of the drilling fluid are at a relatively low level among the indicators of various friction reducers, that is, the LZA-818 friction reducer does not significantly improve the internal structural strength of the fresh water-based drilling fluid; however, after the LZA-818 friction reducer is added to the drilling fluid, the increase in its apparent viscosity and plastic viscosity is relatively obvious.

[0093] The lubrication coefficient of experimental slurry 2-5 with LZA-818 friction reducer added to the brine-based slurry is the minimum among all experimental slurries. Its plastic viscosity is only second to that of experimental slurry 2-2. Therefore, in the brine environment, LZA-818 has strong lubricating film-forming ability and large lubricating film strength, and the effect of improving the lubricating ability of drilling fluid is remarkable.

[0094] In summary, the performance of LZA-818 friction reducer is relatively good in both fresh water-based slurry and brine-based slurry.

[0095] 8. Tests of LZA-818 in different types of drilling fluid systems

[0096] Select LZA-818 friction reducer and four friction reducers with better performance, and test their performance in polymer drilling fluid, polysulfonate drilling fluid and high-performance environmental protection drilling fluid respectively, and conduct comparative analysis.

[0097] 1) Comparative test of the performance of LZA-818 and traditional drilling fluid in polymer drilling fluid system

[0098] Add deionized water, LZA-818 and four common friction reducers to the 1# and 2# polymer drilling fluid systems in sequence, with an addition amount of 2%, and compare their performance differences.

[0099] The experimental results are shown in Table 2-5.

[0100] Table 2-5 Comparative results of the performance of LZA-818 and traditional drilling fluid friction reducers in polymer drilling fluid system

[0101]

[0102] As can be seen from Table 2-5, in terms of lubrication coefficient, the performance of LZA-818 friction reducer in 1# polymer drilling fluid is better than that of other traditional drilling fluid friction reducers in 1# polymer drilling fluid; in terms of shear force, the ability of LZA-818 friction reducer to improve the strength of the internal network structure of drilling fluid is also relatively prominent. At the same time, the performance of LZA-818 friction reducer in enhancing the strength of the lubricating film formed by friction reducer in 1# polymer drilling fluid is also relatively prominent.

[0103] Similar to the above results, the performance of LZA-818 friction reducer in 2# polymer drilling fluid is also relatively good; the test results in terms of shear force and viscosity can also reflect that LZA-818 friction reducer has relatively prominent performance in improving the strength of the internal network structure and lubricating film of drilling fluid.

[0104] In summary, LZA-818 friction reducer has good compatibility and strong friction reduction ability in polymer drilling fluid.

[0105] 2) Performance Comparison Test of LZA-818 and Traditional Friction Reducers in Polysulfonate Drilling Fluid System

[0106] Add LZA-818 and traditional friction reducers into No. 1 and No. 2 polysulfonate drilling fluid systems, with an addition amount of 2%.

[0107] The experimental results are shown in Table 2-6.

[0108] Table 2-6 Performance Comparison Results of LZA-818 and Traditional Drilling Fluid Friction Reducers in Polysulfonate Drilling Fluid System

[0109]

[0110]

[0111] As can be seen from Table 2-6, in terms of the lubrication coefficient, the LZA-818 friction reducer has the best compatibility and the best performance in the No. 1 polysulfonate drilling fluid compared with several other traditional drilling fluid friction reducers; in terms of shear force, after adding the LZA-818 friction reducer into the No. 1 polysulfonate drilling fluid, the strength of its internal network structure is better than that of several other traditional drilling fluid friction reducers in the No. 1 polysulfonate drilling fluid, and the performance of the LZA-818 friction reducer in enhancing the strength of the lubricating film formed by the friction reducer in the No. 1 polysulfonate drilling fluid is also relatively good [5]. Similar to No. 1, the friction reduction ability of the LZA-818 friction reducer also performs well in the No. 2 polysulfonate drilling fluid; from the test results of shear force and viscosity, the performance of the LZA-818 friction reducer in enhancing the strength of its internal network structure and lubricating film in the No. 2 polysulfonate drilling fluid is also stronger than that of other types of friction reducers.

[0112] In summary, the LZA-818 friction reducer has good compatibility and strong friction reduction ability in polysulfonate drilling fluid. 3) Performance Comparison Test of LZA-818 and Traditional Friction Reducers in High-Performance Environmentally Friendly Drilling Fluid System Add LZA-818 and traditional friction reducers into the high-performance environmentally friendly drilling fluid system, with an addition amount of 2%. The experimental results are shown in Table 2-7.

[0113] Table 2-7 Performance Comparison Results of LZA-818 and Traditional Drilling Fluids in High-Performance Environmentally Friendly Drilling Fluid System

[0114]

[0115]

[0116] As can be seen from Table 2-7, in terms of the lubrication coefficient, the performance of the LZA-818 friction reducer in the high-energy environmentally friendly drilling fluid is better than that of several other traditional drilling fluid friction reducers in the high-energy environmentally friendly drilling fluid; the ability of the LZA-818 friction reducer to improve the strength of the internal network structure of the drilling fluid is also relatively prominent; the performance of the LZA-818 friction reducer in the high-energy environmentally friendly drilling fluid to improve the strength of the lubricating film formed by the friction reducer is better than that of several other traditional drilling fluid friction reducers in the high-energy environmentally friendly drilling fluid.

[0117] Figure 5 The change in the lubrication coefficient of the friction reducer samples with different proportions during application in the Wulalik shale reservoir is as Figure 5 shown. It can be seen that adding friction reducer samples with different proportions can reduce the lubrication coefficient of the on-site drilling and completion fluid. The lowest addition amount is 2%, and the lubrication coefficient has dropped below 0.11, with good results. However, due to a large amount of solids in the friction reducer, too high an addition amount will cause the lubrication coefficient to rise. Therefore, the optimal addition amount is 2%. At the same time, during the test, this friction reducer sample has no impact on the stability of the drilling and completion fluid system and will not affect the properties such as the reservoir protection of the drilling and completion fluid system.

[0118] In summary, the LZA-818 friction reducer has good adaptability in the high-performance environmentally friendly drilling fluid and strong friction reduction ability.

[0119] For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and without departing from the spirit or basic characteristics of the present invention, the present invention can be implemented in other specific forms. Therefore, the embodiments should be regarded as exemplary and non-limiting. The scope of the present invention is defined by the appended claims rather than the above description. Therefore, all changes falling within the meaning and scope of the equivalent elements of the claims are intended to be included in the present invention. Any reference signs in the claims should not be regarded as limiting the claimed rights.

Claims

1. A preparation method of a water-based drilling fluid friction reducer containing nanomaterials, characterized in that, It includes the following steps: S1. Select rapeseed oil as the raw material of the base oil, and introduce sulfur ions into the structure through a modification method to prepare a sulfurized rapeseed oil base oil; S2. Select alumina, iron oxide and magnesium oxide to carry out an esterification reaction under high-temperature catalysis. Put the friction reducer sample into a preheated water bath, and add the pre-prepared glyceryl stearate to adjust the viscosity of the drilling fluid after adding it to the friction reducer to prepare an additive; S3. Under the condition of water bath heating, add N-hydroxysuccinimide to N,N'-dicyclohexylcarbodiimide. N-hydroxysuccinimide reacts with N,N'-dicyclohexylcarbodiimide to form an active ester. Then, under the condition of oil bath heating, add the activated N-hydroxysuccinimide to the rapeseed oil containing nanometer tungsten disulfide and stir to react to obtain N-hydroxysuccinimide-modified nanometer tungsten disulfide; S4. Slowly add the additive obtained in step S2 and the N-hydroxysuccinimide-modified nanometer tungsten disulfide obtained in step S3 to the sulfurized rapeseed oil base oil preheated in an oil bath pot according to a ratio, stir and react to obtain a water-based drilling fluid friction reducer.

2. The preparation method of the water-based drilling fluid friction reducer containing nano materials according to claim 1, characterized in that, In step S2, the mass fraction of alumina is 0.1%, the mass fraction of iron oxide is 0.02%, and the mass fraction of magnesium oxide is 0.2%; the mass fraction of glyceryl stearate is 7%.

3. The preparation method of the water-based drilling fluid friction reducer containing nano-materials according to claim 1, characterized in that, In step S3, under the condition of a water bath at 80 °C, add N-hydroxysuccinimide to N,N'-dicyclohexylcarbodiimide, stir and react at 500 r / min for 6 h. Under the condition of oil bath heating at 120 °C, add 10 ml of activated N-hydroxysuccinimide to the rapeseed oil with a mass fraction of 20% nanometer tungsten disulfide and stir and react at 500 r / min for 6 h to obtain N-hydroxysuccinimide-modified nanometer tungsten disulfide.

4. The preparation method of the water-based drilling fluid friction reducer containing nano materials according to claim 1, characterized in that, In step S4, the sulfurized rapeseed oil base oil is preheated to 120 °C and stirred and reacted at 500 r / min for 6 h.

5. The preparation method of the water-based drilling fluid friction reducer containing nano-materials according to claim 1, characterized in that In step S2, the esterification reaction equation is as follows: XO + 2R-COOH → (catalyst, heating) X(R-COO)2 + H2O.

6. The preparation method of the water-based drilling fluid friction reducer containing nanomaterials according to claim 1, characterized in that, In step S1, the mass fraction ratio is 0.1% alumina powder, 0.02% iron oxide powder, 0.2% magnesium oxide powder, 5% N-hydroxysuccinimide-modified nanometer tungsten disulfide, and 7% glyceryl stearate.

7. A water-based drilling fluid friction reducer containing nanomaterials prepared by the preparation method of the water-based drilling fluid friction reducer containing nanomaterials according to any one of claims 1-6, characterized in that, Use rapeseed oil as the raw material for preparing the base oil; the main chain of the molecular structure of the water-based drilling fluid friction reducer is a C-C single bond structure, and the average bond energy of the C-C single bond is 347.3 kJ / mol. Introduce S element into the structure through a sulfurization method to form S=C=S or S≡C≡S bonds. The bond energy of the carbon-sulfur double bond is 536 kJ / mol, and the bond energy of the carbon-sulfur triple bond is 577 kJ / mol to obtain a high-temperature-resistant sulfurized rapeseed oil; at the same time, introduce Fe, Al and Mg elements into the polymer to form metal bonds and covalent bonds between carbon and metals to form a lubricating film with higher strength, and finally add N-hydroxysuccinimide-modified nanometer tungsten disulfide.